Crohn's disease shared decision making intervention leads to more patients choosing combination therapy: a cluster randomised controlled trial. Issue 2 (14th November 2022) - Zisman‐Ilani, Yaara; Thompson, Kimberly D.; Siegel, Lori S.; Mackenzie, Todd; Crate, Damara J.; Korzenik, Joshua R.; Melmed, Gil Y.; Kozuch, Patricia; Sands, Bruce E.; Rubin, David T.; Regueiro, Miguel D.; Cross, Raymond; et al.
Summary: Background: Crohn's disease requires effective patient‐clinician communication for successful illness and medication management. Shared decision making (SDM) has been suggested to improve communication around early intensive therapy. However, effective evidence‐based SDM interventions for Crohn's disease are lacking, and the impact of SDM on Crohn's disease decision making and choice of therapy is unclear. Aim: To test the impact of SDM on choice of therapy, quality of the decision and provider trust compared to standard Crohn's disease care. Methods: We conducted a multi‐site cluster randomised controlled trial in 14 diverse gastroenterology practices in the US. Results: A total of 158 adult patients with Crohn's disease within 15 years of their diagnosis, with no prior Crohn's disease complications, and who were candidates to receive immunomodulators or biologics, participated in the study. Among these, 99 received the intervention and 59 received standard care. Demographics were similar between groups, although there were more women assigned to standard care, and a slightly shorter disease duration among those in the intervention group. Participants in the intervention group more frequently chose combination therapy (25% versus 5% control, p < 0.001), had a significantly lower decisional conflict ( p < 0.05) and had greater trust in their provider ( p < 0.05). Conclusions: With rapidly expanding medication choices for Crohn's disease and slow uptake of early intensive therapy, SDM can personalise treatment strategies and has the potential to move the field of Crohn's disease management forward with an ultimate goal of consistently treating this disease early and intensively in appropriate patients. Trial Registration : Evaluating a Shared Decision Making Program for Crohn's Disease, ClinicalTrials.gov Identifier NCT02084290 https://clinicaltrials.gov/ct2/show/NCT02084290 . Abstract : Shared decision making impacts treatment decisions for patients with Crohn's disease.